Effect of Periodic Exposure to Formaldehyde in the Anatomy Laboratory on some Plasma Protein Levels in Male Wistar Rats - F. O. Ebojele; E. O. Aihie (Journal of Applied Sciences and Environmental Management)
The objective of this paper is to evaluate the effect of periodic exposure to formaldehyde in the anatomy laboratory on some plasma protein levels in male Wistar rats using appropriate standard procedures. Data obtained showed that formaldehyde air level were 0.06±0.00 ppm (parts per million) at the control site, 0.47±0.02 ppm in the dissection hall on non-dissection days, and 1.95±0.02 ppm in the dissection hall on dissection days. Plasma levels of albumin, globulin and fibrinogen were 4.76±0.13 g/l, 3.12±0.07 g/l and 1.04±0.16 g/l respectively on non-dissection days and 5.06±0.07 g/l, 3.24±0.06 g/l and 1.18±0.18 g/l respectively on dissection days. Results revealed significant increase in the atmospheric levels of formaldehyde in the dissection hall but the plasma protein levels showed no significant difference. In conclusion, exposure to formaldehyde in the Anatomy laboratory may not affect plasma protein levels in Wistar rats.